1989
DOI: 10.1016/0021-9797(89)90210-5
|View full text |Cite
|
Sign up to set email alerts
|

Monomer-addition growth with a slow initiation step: A growth model for silica particles from alkoxides

Abstract: A simplified monomer-addition model with a first-order activation step is developed to describe the dynamics of growth of silica particles from alkoxides. In the fimit of slow hydrolysis, we obtain expressions for the evolution of the particle mass and particle polydispersity, as well as an expression for the particle size as a function of the hydrolysis rate constant, the polymerization rate constant, and the initial concentration of the orthosilicate. We find that the formation of the particles is adequately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 9 publications
1
142
0
1
Order By: Relevance
“…At this time, no definitive explana- tions can be offered for these trends. However, it is not unreasonable to expect that, as in the case of silica formation in homogeneous alcohol-alkoxide systems (31,(41)(42)(43)(44)(45), the observed particle size dependence on ammonia concentration may be related to the ability of the OH Ϫ ion (generated by the hydrolysis of ammonia) to catalyze both hydrolysis and condensation reactions and the tendency for siloxane bonds to break in highly alkaline solutions (32,35,39).…”
Section: Amphiphilic Nature Of Partially Hydrolyzed Teosmentioning
confidence: 93%
“…At this time, no definitive explana- tions can be offered for these trends. However, it is not unreasonable to expect that, as in the case of silica formation in homogeneous alcohol-alkoxide systems (31,(41)(42)(43)(44)(45), the observed particle size dependence on ammonia concentration may be related to the ability of the OH Ϫ ion (generated by the hydrolysis of ammonia) to catalyze both hydrolysis and condensation reactions and the tendency for siloxane bonds to break in highly alkaline solutions (32,35,39).…”
Section: Amphiphilic Nature Of Partially Hydrolyzed Teosmentioning
confidence: 93%
“…By following the variance of the size distribution as a where L x 0 and L y 0 are the initial diameters of the two seeds function of the mean particle diameter with TEM, Matsoukas and L xt and L yt are diameters at t minutes after the growth and Gulari (6) found that the variance (s 2 ) was proportional starts. to the mean particle's diameter with an exponential of 01.75 Equation [3] indicates that the difference in diameters of { 0.2, very close to 02, indicating a surface reaction-limited the two seeds keeps constant during growth.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of Stöber method with respects to silica particle formation, growth, and particle size, distribution, and shape have been investigated in the past decades [30][31][32][33][34][35][36][37][38][39][40][41][42]. However, the mechanisms reported by different researchers are contradictory.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al summarized the mechanisms from literatures which may be sorted into two different models: the monomer addition model and the controlled aggregation model [42]. The monomer addition model argues that after a limited period of time for nucleation, growth occurs through the addition of hydrolyzed monomers to the oligomers surface and gradually becomes the dominant process [30,33,34]. On the contrary, the controlled aggregation model claims that the aggregation of sub-particles leads to particle formation [31,32,37,40,41].…”
Section: Resultsmentioning
confidence: 99%